Health promotion in elite para sport: bridging knowledge gaps and addressing individual needs—a qualitative evaluation of the safe and healthy para sport (SHAPE) intervention - Halvorsen Wik, E.; Kenttä, G.; Badenhorst, M.; Derman, W.; Eken, M.; Kunorozva, L.; Lexell, J.; Runciman, P.; Fagher, K. (British Journal of Sports Medicine, 2025)
Objective To qualitatively explore the perceptions of Para athletes, coaches and stakeholders of the implementation, use and effects of the health promotion intervention `Safe and Healthy Para sport` (SHAPE). A secondary aim was to explore participants` perceptions of how safety and health in Para sport could be further developed.